PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS XII IPS SMA NEGERI 3 SURABAYA MENGGUNAKAN PENDEKATAN COOPERATIVE LEARNING - S. W. Embun Waty (Universitas Muhammadiyah Surabaya, 2007)
ABSTRAKTeching speaking is not very easy to handle, while the result is not always satisfied and significant. One of the reasons for teachers not to teach speaking is that in the national test, speaking is not examined. Another important reason is that teacher are not very. Enthusiastic to teach speaking because it needs time to prepare and it’s time consumingto handle in a class of to students or more. This research tries to give alternative in teaching speaking through cooperative learning. Studentare divided into groups of 4 students. Each group has to prepare a text with the theme they can select themselves. The text they have writtenhas to be presented in front of the class, while the other students of the class are to respond by giving questions, comments, opinions, or suggestion. The group which presents has to answer the questions or responds the comments. Through this activity the teacher can make the evaluation on the grammar/structure, pronounciation, accuracy, fluency, and also the vocabulary, while the cooperative learning strategy can make the students happy, cooperate and share with other members of their group, and the most important thing that students are motivated to speak much and feel confident. They are motivated to produce more talksthrough the theme which is usually actual and popular among them such as culture, drugsabuse, motor racing.